تحليل العلاقة الاقتصادية بين العرض النقدي وتقلبات سعر الصرف ومؤشر التضخم في الجزائر خلال الفترة ( 1970-2019) - جدي, العربي; قطاف, عبدالقادر (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى تحليل العلاقة الاقتصادية بين مؤشر التضخم INF والعرض النقدي الموسع M2 ومتغيرة سعر الصرف TC وفق منهجية التكامل المشترك،توصلت النتائج إلى وجود سببية في اتجاه واحد خلال المديين القصير والطويل من TC ومؤشر INF نحو متغيرة M2 في نموذج VECM ، تبين أن سعر الصرف TCيؤثر إيجابا على العرض النقدي الموسع M2في الأجل القصير ،حیث إذا تغير TC بـ 1% تغير M2 بـ 0.18%، بينما مؤشر التضخم كان تأثيره في المدى الطويل عند زيادته بحوالي1% يرتفع العرض النقدي بحوالي 2.68%. أما معامل تصحیح الخطأ بلغ وهو ذو دلالة إحصائية واقتصادية. This study aims to analyze the economic relationship between the (INF) inflation index and the expanded monetary supply (M2) and the exchange rate variable (TC) according to the methodology of joint integration. The results found a one-way causality in the short and long term of (TC) and (INF) towards the (M2) variant in the VECM model, showing that the (TC) exchange rate positively affects the extended (M2) short-term cash supply, where if (TC) changes by 1% change (M2) by 0.18%, while the inflation index has had a long-term impact when it increases by about 1%, the cash supply increases by about 2.68%. The error corrective coefficient is (02%), which is statistically and economically significant.
Analysis of the economic relationship between M2 money supply and TC fluctuations and INF inflation index in Algeria During the period (1970-2019)
مقال
Keywords: المتغيرات الاقتصادية.، استقرارية السلاسل الزمنية.، السببية.; VECM.